TRÁFICOS DE ANIMAIS SILVESTRES: PERCEPÇÃO AMBIENTAL COM DISCENTES DE UMA ESCOLA DO ENSINO MÉDIO DE PARNAÍBA- PI - Santos, Suely Silva; Pereira, Ocivana Araujo; Sousa, Francisco Eduardo dos Santos; Guzzi, Anderson (Revista Nordestina de Zoologia, 2016)
The main cause of species extinction is deforestation followed by hunting. Many people think that the nature's resources are inexhaustible thus performing predatory hunting. Environmental education in schools aims to engage students in conservation action by being aware of and learning to protect these animals. In this context, environmental education becomes a very important tool for raising awareness of the environment in wich we live. The objective of this article is to conduct a qualitative and quantitative analysis of students' perceptions of a Parnaíba high school about the trafficking of wild animals. This was done through lectures and the application of a semi-structured survey. The research confirms that many students do not know the importance of these animals to the environment and the extent of this problem. The project made actions possible with positive signs of new attitudes incorporated in the school environment, but it was also verified that it still needs continuity in educational institutions and in the community.